FabAV antivenin use after copperhead snakebite: clinically indicated or knee-jerk reaction?. Issue 1 (December 2016) - Gale, Stephen; Peters, Jo; Allen, LaDonna; Creath, Robert; Dombrovskiy, Viktor
Abstract Background Crotalidae Polyvalent Immune Fab (Ovine) (FabAV) antivenin is commonly recommended after pit viper snakebites. Because copperhead envenomations are usually self-limited, some physicians are reluctant to use this costly treatment routinely, while others follow a more liberal approach. We hypothesized that, in practice, only patients with evidence of significant (moderate or severe) copperhead envenomation [those with snakebite severity score (SSS) > 3] receive FabAV and examined a large cohort to determine the relationship between clinical findings and FabAV administration. Methods All data from patients evaluated for copperhead snakebite at a rural tertiary referral center from 5/2002 to 10/2013 were compiled. Demographics, transfer status, antivenin use, and clinical findings were collected; SSS was calculated. The relationships among FabAV use, clinical findings, and SSS were analyzed usingt -test, chi-square, and Pearson's coefficient (p  < 0.05 was significant). Results During the study period, 318 patients were treated for copperhead snakebite; 44 (13.8 %) received antivenin. Median dose was four vials (range: 1–10; IQR: 4, 6). There were no deaths. Most patients receiving FabAV (63.6 %) were admitted. With regard to demographics and symptoms, only the degree of swelling (moderate vs. none/mild;p  < 0.01) and bite location (hand/arm vs. leg:p  < 0.0001) were associated with FabAV use. A SSS > 3, indicating moderate or severe envenomation, was only very weakly correlated with antivenin use (r = 0.217;p  < 0.0001). The majority of patients with SSS > 3 (65.8 %) did not receive antivenin while most patients who did receive antivenin (70.5 %) had SSS ≤ 3 (indicating mild envenomation). Conclusions Considerable variation occurs in antivenin administration after copperhead snakebite. Use of FabAV appears poorly correlated with patients' symptoms. This practice may expose patients to the risks of antivenin and increasing costs of medical care without improving outcomes. Guidelines used for treating other pit viper strikes, such as rattlesnake or cottonmouth snakebite may be too liberal for copperhead envenomations. Our data suggests that most patients with mild or moderate envenomation appear to do well independent of FabAV use. We suggest, for patients with copperhead snakebite, that consideration be given to withholding FabAV for those without clinical evidence of severe envenomation until prospective randomized data are available.